KESEIMBANGAN KERJA: Kepuasan Dosen dalam Kaitannya dengan Faktor-Faktor Kerja - Wahyudi, Wahyudi (Sekolah Menengah Kejuruan (SMK) Pustek, 2024)
This research delves into the critical role of higher education in shaping human resources and advancing a nation. A key determinant of the quality of higher education lies in the satisfaction of lecturers, whose performance is intricately linked to various work-related factors. This study specifically investigates the influence of compensation, leadership, policies, work environment, and facilities on lecturers' satisfaction, aiming to provide insights that can enhance the welfare and effectiveness of educators within higher education institutions. Employing a qualitative approach with survey techniques, the research utilizes a questionnaire as the primary instrument distributed to randomly selected lecturers at Pamulang University, considering predetermined criteria. The sample comprises respondents from diverse fields of study, facilitating a comprehensive understanding of the issues at hand. Data analysis relies on descriptive statistics to delineate the level of lecturer satisfaction with each scrutinized work factor. The findings reveal that lecturer satisfaction with compensation and the work environment is commendable, achieving an average score of 4.40. These two factors emerge as the primary drivers fostering improved lecturer performance. Conversely, satisfaction with leadership, policies, and work facilities is deemed reasonably satisfactory, each garnering an average score of 4. These results furnish a holistic portrayal of the work factors necessitating attention to elevate lecturer performance, underlining the importance of strategic focus on these core elements.